Análise da tradução de neologismos referentes ao mundo de fantasia “Temerant” na obra “O nome do vento”, de Patrick Rothfuss, do inglês para o português brasileiro - Colares, Raphael Sampaio (2024)
This work aims to analyze the translation procedures of neologisms found in the literary fantasy world ―Temerant‖, part of the literary work of ―The Name of The Wind‖ (Rothfuss, 2007). This work arises from the need to understand the possible translation strategies adopted for neologisms in the source language that do not have linguistic representation in the target language. The analysis of the procedures will be carried out with English as the source language and Brazilian Portuguese as the target language. The main theoretical basis used were: (1) Nord's theories (2007, 2016) referring to the modern model of functionalist translation as a way of establishing the concepts used here about the translation process; (2) the concepts of Newmark (1988), which contributes to the identification of a neologism, its categorizations and the recognition of possible translation procedures submitted in a neologism; and (3) the conceptions presented by Todorov (1973) about the literary text and its fantastic realities, which are established, whether in the source language or the target language, as a crucial component in the identification and understanding of translated and analyzed communication. Furthermore, as a fundamental part of the analysis, a list of neologisms from the book ―The Name of The Wind‖ was created; making it possible to identify a series of characteristics that helped to study the translation procedures used and to understand their consequences. According to the methodology used in the search for neologisms, a total of 81 neologisms were analyzed, resulting in the identification of 114 different translation procedures.